2012
DOI: 10.1371/journal.pone.0046859
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nongenomic Signaling by Glucocorticoid May Involve Changes to Liver Membrane Order in Rainbow Trout

Abstract: Stress-induced glucocorticoid elevation is a highly conserved response among vertebrates. This facilitates stress adaptation and the mode of action involves activation of the intracellular glucocorticoid receptor leading to the modulation of target gene expression. However, this genomic effect is slow acting and, therefore, a role for glucocorticoid in the rapid response to stress is unclear. Here we show that stress levels of cortisol, the primary glucocorticoid in teleosts, rapidly fluidizes rainbow trout (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…This is in agreement with our recent finding that cortisol treatment in vitro rapidly fluidizes liver plasma membrane and activates stress-related signaling pathways in trout hepatocytes (12). Most studies have focused on the genomic actions of cortisol in stress adaptation (2), whereas this study highlights a novel rapid action of cortisol that may be nongenomic and involves membrane structure alterations and modulation of stress-related signaling pathways in trout liver.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is in agreement with our recent finding that cortisol treatment in vitro rapidly fluidizes liver plasma membrane and activates stress-related signaling pathways in trout hepatocytes (12). Most studies have focused on the genomic actions of cortisol in stress adaptation (2), whereas this study highlights a novel rapid action of cortisol that may be nongenomic and involves membrane structure alterations and modulation of stress-related signaling pathways in trout liver.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, we reported that in vitro exposure to cortisol rapidly alters fluidity, surface topography, and elasticity of hepatic plasma membranes in rainbow trout (Oncorhynchus mykiss) (12). In addition to modulating plasma membrane properties, stress levels of cortisol rapidly phosphorylated putative substrate proteins of protein kinase C (PKC), protein kinase A (PKA), and Akt in hepatocytes.…”
mentioning
confidence: 99%
See 3 more Smart Citations